THE EFFECT OF “SCHEMA DEVELOPMENT TECHNIQUE” ON STUDENTS’ READING ABILITY AT SENIOR HIGH SCHOOL STUDENT - Deni Widiarti; Bambang Suwarno; Dedi Sofyan (Universitas Bengkulu, 2018)
This study aimed to find the effect of “schema development technique” on students’ reading ability at senior high school students. It is also aimed to find whether schema development technique could improve students’ reading ability on the aspect of literal comprehension, inference and vocabulary building. The population was the tenth graders of SMA Negeri Rejang Lebong, from which two classes were selected as the research sample. The instrument was a reading test. The instrument draft had been tried out. The try out was done to find the validity and item characteristics of the original draft. From 90 try out item questions, 42 of them were found to be valid and 48 were invalid. The reliabilty index was 0,898 (high). The findings of the research revealed that schema development technique was effective for improving students overall comprehension. It was also effective for improving two aspects (literal aspect and vocabulary building). However, it was not effective for improving students’ reading ability on inference aspect. It’s caused by the nature of inference which requires for background knowledge towards the reading text.